Psycho-criminological approaches to stalking behavior : an international perspective - Chan, Heng Choon, 1981-; Sheridan, Lorraine (Wiley series in psychology of crime, policing, and law., 2020)
"This work is only a start. The perceptive reader will quickly discern that many countries are not represented by the roster of authors, more specifically, large swaths of South America, Africa, the Middle East, and Asia. This book is a tremendous start-two internationally recognized experts in stalking are the co-editors--but there is much work to be done to codify stalking as a crime in most countries of the world where it is not; a fact which brings me to my first point in this foreword. A prerequisite of stalking is a stable democracy wherein other, and often more severe forms, of interpersonal violence have already been addressed in criminal law. Some authors have referred to these as the WEIRD (westernized, educated, industrialized, rich, and democratic) countries, suggesting a certain ppejorativeattitude toward them; my preference is to consider them WIRED, suggesting both progression and innovation"--